Unpicking observational relationships between hip shape and osteoarthritis: hype or hope?. Issue 1 (January 2020) - Faber, Benjamin G.; Frysz, Monika; Tobias, Jon H.
Abstract : Purpose of review: To review recent findings concerning the observational relationship between hip shape and hip osteoarthritis (HOA) and their shared genetic influences, and the potential for clinical application. Recent findings: Recent observational studies have strengthened the evidence that specific shape deformities, such as cam and acetabular dysplasia, are related to HOA. Statistical shape modelling has emerged as a method to measure hip shape holistically, with the added advantage that this can be applied to dual X-ray absorptiometry scan images. This has led to several additional aspects of hip shape variation being identified, such as a wider femoral neck and larger lesser trochanter, in association with HOA. Furthermore, this method has formed the basis of genetic studies identifying novel genetic influences on hip shape, several of which are shared with known genetic risk factors for HOA. Summary: Shared genetic influences of hip shape and HOA raise the possibility that hip shape plays a casual role in the development of HOA, justifying preventive approaches aiming to combat these adverse consequences.